Visualization of electron temperature and density isosurfaces or isocurves in Tokamak plasmas - F. Salzedas (2005)
In this paper are described two programs that allow the easy visualization of isosurfaces S(r,t) or isocurves C(r,t), time and space profiles from electron temperature and density of Tokamak plasmas, used in research of thermonuclear fusion of light nucleus. The programs are written in IDL and they run in two European laboratories, JET (Joint European Torus) that is the largest Tokamak in the world, based in the UK and ASDEX Upgrade a German Tokamak, based at the IPP Max Plank Institute near Munich.The user interface is graphical and is similar on both programs in order to facilitate its usage. A Fourier analysis module is included to allow a quick visualization of spectrogram from channels and compare them with isosurfaces. This analysis is very useful to detect plasma instabilities. Any of these programs can be applied to any other kind of data with the same structure S(r,t).